2002
DOI: 10.1039/b210065g
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of three-dimensional chromium oxide porous single crystals templated by SBA-15

Abstract: Three-dimensional porous chromium oxide single crystals have been prepared by aminosilylation of the surface silanols of the template, SBA-15, anchoring of dichromic acid to the grafted amine groups, thermal decomposition of inorganic and organic compounds, and removal of the silica framework with HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
134
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(152 citation statements)
references
References 14 publications
8
134
0
Order By: Relevance
“…In our previous work, we found that the mesochannels of SBA-15 and KIT-6 were far from completely filled by metal precursors due to a large loss of Si-OH groups during the organic template removal process that involved a thermal calcination, 40,41 and this phenomenon has also been reported by other groups. 35,42,43 Other approaches such as using solvents and supercritical fluid extraction require long periods of operation (.24 h) and it is difficult to remove the organic template completely. 44 Tian et al proposed microwave irradiation as an effective technique for making organic templates such as Pluronic P123 quickly and with total removal of the onedimensional (1D) SBA-15 material with the greatest preservation of the original mesoporous structure and surface hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous work, we found that the mesochannels of SBA-15 and KIT-6 were far from completely filled by metal precursors due to a large loss of Si-OH groups during the organic template removal process that involved a thermal calcination, 40,41 and this phenomenon has also been reported by other groups. 35,42,43 Other approaches such as using solvents and supercritical fluid extraction require long periods of operation (.24 h) and it is difficult to remove the organic template completely. 44 Tian et al proposed microwave irradiation as an effective technique for making organic templates such as Pluronic P123 quickly and with total removal of the onedimensional (1D) SBA-15 material with the greatest preservation of the original mesoporous structure and surface hydroxyl groups.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Growth of metal oxides in pores of mesoporous silica can result in nanowires or porous single crystals. 13,14 In this case, the crystal growth is confined by the pore size. One dimensional growth to form nanorods or nanowires can also be achieved by surface protection with ligands, 15,16 or by using porous templates such as anodic aluminum oxide.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al successfully prepared various mesoporous metal oxides using organic functionalized mesoporous silica as template that involves the adsorption of inorganic precursors onto the amine-functionalized mesoporous silica materials and the thermal decomposition of the precursor to assemble the individual metal hydroxide nanoparticles in the mesochannels followed by subsequent removal of the amine-functionalized silica by hydrofluoric acid. 169 Various mesoporous metal oxides such as Cr 2 O 3 , V 2 O 5 , WO 3 , and Fe 2 O 3 with ordered structure were synthesized using this strategy by choosing appropriate metal precursor solutions.…”
Section: Component Innovationmentioning
confidence: 99%